Sleep Deprivation in Negotiations: A Mixed-Method Investigation - Halfmann, Emma; Justus Liebig University Giessen (My University, 2022)
Negotiations are often used as conflict resolution in a society that is increasingly sleep-deprived. Yet, not much is known about how sleep deprivation affects negotiations. In this dissertation, I present and test a theoretical framework for understanding and investigating the effects of sleep deprivation on various negotiation processes and outcomes, particularly joint economic outcomes, individual economic outcomes, social perceptions and emotions, and impasses. Focusing on integrative negotiations, I identified cognitive capacities and epistemic motivation to be highly relevant psychological processes, affected by sleep deprivation in negotiation. These impairments deteriorate effective information exchange and hamper information processing, which reduces the quality of (integrative) agreements. In four quantitative studies and one qualitative study, the hypothesized effect of sleep deprivation on the quality of negotiation agreements in terms of joint economic outcomes was tested. In three experiments (total N = 398), sleep-deprived versus well-rested dyads participated in (Studies 1 and 2) or observed (Study 3) an integrative negotiation. In all three studies and a Bayesian meta-analysis across these, there was no effect of sleep deprivation on agreement quality. These findings contradict theoretical predictions and also laypersons’ expectations (Study 4). However, there was an indication for compensatory effort that could account for the absence of a substantial negative effect of sleep deprivation. To gain further insights, qualitative interviews with 22 German elected politicians were conducted (including head of state and federal ministers) who are experienced in negotiations under sleep deprivation (Study 5). Their responses shed light on the nature of compensatory strategies that might help to cope with sleep deprivation in real-life negotiations. To explain the findings, potential moderators on the task, the individual, and the inter-individual level are discussed, which help to understand how sleep deprivation-induced impairments could be compensated for. In sum, my dissertation aims to advance the understanding of how sleep deprivation negatively affects negotiation outcomes.
Keywords: Negotiation; Sleep deprivation; ddc:150